Personality and city culture predict attitudes and practices toward mosquitoes and mosquito-borne diseases in South Texas - Amy K. Bohmann; Lisset Martinez-Berman; Amy R. Senger; Megan R. Wise de Valdez (Frontiers in Public Health, 2022)
Personality is known to affect compliance with health-protective behaviors and it has been shown that effective public health messaging can be informed by an understanding of that relationship. Thus, we aimed to evaluate the role personality might play in implementing personal protective measures (PPMs) that can prevent mosquito-borne diseases. This is the first mosquito-related knowledge, attitudes, and practices (KAP) study to incorporate a measure of personality using the Big Five: openness, conscientiousness, extraversion, agreeableness, and neuroticism. KAP studies in Gulf-coast and Mexican border-states in the U.S. are few. Ours is only the second KAP study to take place in Texas despite known local transmission and established mosquito populations capable of transmitting dengue, zika, chikungunya, and West Nile viruses. The KAP survey was administered in three neighborhoods in San Antonio, a large, Hispanic-majority, urban city that is segregated economically and ecologically. We found that openness, agreeableness, and extraversion predicted certain attitudes and PPMs, and that KAP and personality measures did not differ along ethnic or neighborhood lines. Perceptions toward the city's role in mosquito control and education was an important factor in predicting PPMs, suggesting that city culture (attitudes common throughout the city as opposed to attitudes differing by ethnicity and neighborhood) may be most salient in developing public health messaging in San Antonio.